Type specimen sequencing, multilocus analyses, and species delimitation methods recognize the cosmopolitan Corallina berteroi and establish the northern Japanese C. yendoi sp. nov. (Corallinaceae, Rhodophyta) - Calderon, Martha S (Journal of phycology, 2021)
© 2021 Phycological Society of America.